Application of high-throughput screening to identify a novel αIIb-specific small- molecule inhibitor of αIIbβ3-mediated platelet interaction with fibrinogen - Blue, Robert (American Society of Hematology, 2008)
Small-molecule αIIbβ3 antagonists competitively block ligand binding by spanning between the D224 in αIIb and the MIDAS metal ion in β3. They variably induce conformational changes in the receptor, which may have undesirable consequences. To identify αIIbβ3 antagonists with novel structures, we tested 33 264 small molecules for their ability to inhibit the adhesion of washed platelets to immobilized fibrinogen at 16 μM. A total of 102 compounds demonstrated 50% or more inhibition, and one of these (compound 1, 265 g/mol) inhibited ADP-induced platelet aggregation (IC(50): 13± 5 μM), the binding of soluble fibrinogen to platelets induced by mAb AP5, and the binding of soluble fibrinogen and a cyclic RGD peptide to purified αIIbβ3. Compound 1 did not affect the function of GPIb, α2β1, or the other β3 family receptor αVβ3. Molecular docking simulations suggest that compound 1 interacts with αIIb but not β3. Compound 1 induced partial exposure of an αIIb ligand-induced binding site (LIBS), but did not induce exposure of 2 β3 LIBS. Transient exposure of purified αIIbβ3 to eptifibatide, but not compound 1, enhanced fibrinogen binding (“priming”). Compound 1 provides a prototype for small molecule selective inhibition of αIIbβ3, without receptor priming, via targeting αIIb.